Sole Excited-State InAs Quantum Dot Laser on Silicon With Strong Feedback Resistance - Chen, Jia-Jian; Wang, Zi-Hao; Wei, Wen-Qi; Wang, Ting; Zhang, Jian-Jun (Frontiers in Materials, 2021)
Feedback insensitive laser is a prerequisite of desirable laser source for silicon photonic integration, as it is not possible to include an on-chip optical isolator. This work investigates the feedback insensitivity of an InAs/GaAs quantum dot laser epitaxially grown on Si (001) substrate by operating in sole excited state. The experimental results show that the sole excited-state lasing InAs quantum dot lasers on Si are less sensitive to external optical feedback than both fabry-perot and distributed feedback quantum well lasers. By comparing the laser behavior under different feedback levels, sole excited-state InAs quantum dot laser on Si exhibit at least 28 dB stronger feedback tolerance than quantum well lasers. This result proposes a possible route for a highly feedback-insensitive laser for on-chip light source towards Si waveguide integration with absence of an optical isolator.